Dialogue and Structure: Enabling Learner Self-Regulation in Technology-Enhanced Learning Environments. (October 2014) - Andrade, Maureen Snow
Distance learning that incorporates technology-enhanced learning environments provides a solution to the ever-increasing global demand for higher education. To be successful in these contexts, learners must be self-regulated, or have the ability to control the factors affecting their learning. Based on the theories of transactional distance, self-regulated learning (SRL) and language acquisition, the model of self-regulated distance learning has been shown to increase learner self-regulation and success. The current exploratory study examined the role of dialogue and structure on the effectiveness of SRL activities in an English language course based on this model. The study examined student responses and related teacher feedback to SRL activities as well as course structural components to determine how dialogue (i.e. teacher feedback) and structure helped or hindered learners in gaining full benefit from the SRL course component. Findings indicated that a lack of dialogue and missing structural elements were related to students completing the activities superficially, with inappropriate sequencing, or not doing them at all. Across the two semesters studied, the teachers varied in the extent and quality of their feedback, and structural problems undermined the value of the activities. Consequently, changes were made in course set-up and teacher training provided.